Nós negros: a literatura da diáspora africana nas Américas e seus elementos em comum - Pereira, Gilberto Gomes (2023)
Literature can help us to understand the world. In this case, the novels are in a privileged place to accomplish it. As art, the brightness of the novels come from the aesthetic, but the whole body of the narrative brings out the load of feelings and actions that pulse right in the social relations as well, exploring spaces which sociology knows how to scrutinize. When it is about the afro-descendant literature, no matter where in the Americas the fiction is from, it will always communicate with another fiction created by any other black author in any other place of the Americas, just because of the forced African diaspora aftermaths. Based on this hypothesis, this research proposes an analysis of novels of four black authors from four countries: The Underground Railroad, by the American writer Colson Whitehead, At the full and change of the moon, by the Canadian-Trinidadian Dionne Brand, A brief history of seven killings, by the Jamaican Marlon James, and Alleys of memory, by Brazilian Conceição Evaristo. The aim of it is not to elucidate the complexity of the world of the Americas, built up by the exploitation of the black people in the slavery system, but to problematize sociologically the literature of black voice.